Comportamento coordenado em ratos: efeitos da forma de distribuição do reforço entre indivíduos trabalhando em dupla - Silva, Rafael Fernando da (2022)
The coordinated responding of pairs of rats that occur in close temporal proximity can be conceived as a unit of cooperation which has been shown to be modulated by reinforcement schedules, similar to individual responding. The central question of this study was whether coordinated responding can be maintained when the reinforcers that are dependent on coordination are alternately presented to one of two cooperating rats across cooperative episodes. For this, tandem schedules with two components of Fixed Interval (tandem FI FI) or Variable Interval (tandem VI VI) schedules were used, as the consequences of coordination were alternately provided across the two rats. Individual and mutual reinforcement contingencies were used as experimental controls. Coordinated responses were defined as a unit involving two responses, one of each cooperating member, occurring within an interval of 0.2 s of one another. Each coordinated response was followed by a LED light for an interval of 0.2 s in all experimental conditions. Individual response rates increased systematically throughout experimental sessions and conditions. Although the same schedules were used in all three conditions, the individual reinforcement contingency (in which one’s reinforcer did not depend on its patterning rat) resulted in a higher reinforcement rate. The alternating reinforcement condition maintained coordinated responding, but the rates and proportions of coordinated responses were lower than those observed under conditions in which reinforcement was delivered to the pair members at the same time. This study showed that simultaneity in the delivery of reinforcers to members of the cooperative episode can be a critical variable in the operant selection of coordinated responding in pair of rats.